Clinical utility of target capture‐based panel sequencing in hematological malignancies: A multicenter feasibility study. Issue 9 (17th July 2020) - Yasuda, Takahiko; Sanada, Masashi; Nishijima, Dai; Kanamori, Takashi; Iijima, Yuka; Hattori, Hiroyoshi; Saito, Akiko; Miyoshi, Hiroaki; Ishikawa, Yuichi; Asou, Norio; Usuki, Kensuke; Hirabayashi, Shinsuke; et al.
Abstract: Although next‐generation sequencing‐based panel testing is well practiced in the field of cancer medicine for the identification of target molecules in solid tumors, the clinical utility and clinical issues surrounding panel testing in hematological malignancies have yet to be fully evaluated. We conducted a multicenter prospective clinical sequencing study to verify the feasibility of a panel test for hematological tumors, including acute myeloid leukemia, acute lymphoblastic leukemia, multiple myeloma, and diffuse large B‐cell lymphoma. Out of 96 eligible patients, 79 patients (82%) showed potentially actionable findings, based on the clinical sequencing assays. We identified that genetic alterations with a strong clinical significance were found at a higher frequency in terms of diagnosis (n = 60; 63%) and prognosis (n = 61; 64%) than in terms of therapy (n = 8; 8%). Three patients who harbored a germline mutation in either DDX41 (n = 2) or BRCA2 (n = 1) were provided with genetic counseling. At 6 mo after sequencing, clinical actions based on the diagnostic (n = 5) or prognostic (n = 3) findings were reported, but no patients were enrolled in a clinical trial or received targeted therapies based on the sequencing results. These results suggest that panel testing for hematological malignancies would be feasible given the availability of useful diagnostic and prognostic information. This study is registered with the UMIN Clinical Trial Registry (UMIN000029879, multiple myeloma; UMIN000031343, adult acute myeloid leukemia; UMIN000033144, diffuse large B‐cell lymphoma; and UMIN000034243, childhood leukemia). Abstract : This multicenter prospective study investigated feasibility of target capture‐based panel testing, focusing on hematological malignancies. Our results suggest that panel testing for hematological malignancies is feasible given the availability of useful diagnostic and prognostic information.